Taking Ownership: The Implementation of a Non-Aboriginal Early Education Programme for On-Reserve Children - Michelle Beatch; Lucy Le Mare (The Australian Journal of Indigenous Education, 2007)
Abstract In this qualitative study, over the period of one year, we assessed the appropriateness of a mainstream early childhood education intervention, the Home Instruction for Parents of Preschool Youngsters (HIPPY) programme, in five on-reserve First Nations communities, by focusing on the experiences of the Aboriginal women who delivered the programme. Findings revealed a process of “taking ownership” of HIPPY. “Taking ownership” included three subprocesses: changes in the women’s views regarding (1) the strengths of the programme; (2) self-identity; and (3) the identification of the programme as Aboriginal. Through taking ownership, the women were no longer content to deliver HIPPY strictly as it was described in the programme manuals. Although the women continued to maintain that HIPPY was valuable for their communities, their actions and words clearly demonstrated that sharing cultural knowledge in the context of the programme was important to them and, they believed, important for the children and families they worked with. The process documented here points to the importance of Aboriginal culture reflected in educational provisions for Aboriginal children - whether this can be appropriately achieved through supplementing and/or adapting mainstream programmes remains a point of debate.